1990
DOI: 10.1118/1.596500
|View full text |Cite
|
Sign up to set email alerts
|

Dose perturbations at interfaces in photon beams: Secondary electron transport

Abstract: An improved, quantitative version of the partial fluence model [Med. Phys. 14, 585 (1987)] for the calculation of dose perturbations at media interfaces in photon beams is presented and compared with measurements made at interfaces between polystyrene and materials ranging in atomic number from aluminum to lead, for photon beams ranging in energy from 60Co to 24 MV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Radiation dose perturbations near media interfaces have long been a subject of investigation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] If two media of different atomic number ͑Z͒ are irradiated in contact geometry by a photon beam, there will exist a transition zone in which the electron fluence will be composed of electrons generated in both media. This transition zone may extend from the interface to a few millimeters or even centimeters depending on the energy of the photon beams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation dose perturbations near media interfaces have long been a subject of investigation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] If two media of different atomic number ͑Z͒ are irradiated in contact geometry by a photon beam, there will exist a transition zone in which the electron fluence will be composed of electrons generated in both media. This transition zone may extend from the interface to a few millimeters or even centimeters depending on the energy of the photon beams.…”
Section: Introductionmentioning
confidence: 99%
“…In this region of electronic disequilibrium, significant perturbations in the absorbed dose can occur. Analytic models, 4,5,9 Monte Carlo techniques 2,8,15 and experimental measurements 3,[6][7][8][12][13][14] have been reported to determine these perturbations. Scrimger 16 has measured a 10% dose enhancement in the entrance side ͑backward͒ of tissue-titanium interface for the 60 Co beam and 12% for a 8 MV photon beam using a cylindrical chamber, whereas Tatcher et al 17 have reported a 25% to 40% enhancement at the exit side ͑forward͒ using films.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [7,8,10,12,14,15,17,18] have shown that the dose distribution in the build-up region depends on several factors such as source to skin distance (SSD), field size, presence of secondary blocking tray and the distance between the skin and the blocking tray. A number of studies [2-4, 7, 14, 15] has been carried out by many authors for the early generation linear accelerators and different model cobalt-60 machines.…”
mentioning
confidence: 99%
“…However, the atomic number of Gamma Putty is high (90% bismuth, Z=83), which enhances pair production and changes the spectral distribution of the secondary charged particles. The high atomic number of Gamma Putty also enhances local variation in the angular distribution of secondary electrons, as suggested by several reports [22][23].…”
Section: Discussionmentioning
confidence: 57%